Breaker Morant - Ross, Kenneth 1941- (<<The>> Criterion Collection, 2015)
"Drei im Burenkrieg auf britischer Seite kämpfende Australier werden wegen der Erschießung von Gefangenen in einem manipulierten Kriegsgerichtsverfahren abgeurteilt. Dialogträchtige Rekonstruktion eines historischen Prozesses. Eine Anklage des Kolonialismus und eine differenzierte Auseinandersetzung mit der Frage der moralischen Verantwortung des einzelnen." [filmdienst.de]
Original: Australien 1980
director-approved two-DVD special edition features: new, restored 4K digital transfer, supervised and approved by director Bruce Beresford ; audio commentary from 2004 featuring Beresford ; new interviews with Beresford, cinematographer Donald McAlpine, and actor Bryan Brown ; interview with actor Edward Woodward from 2004 ; new piece about the Boer War with historian Stephen Miller ; "The breaker", a 1973 documentary profiling the real Harry "Breaker" Morant, with a 2010 statement by its director, Frank Shields ; trailer ; plus: an essay by film scholar Neil Sinyard
Bildformat 1.85:1
Keywords: Film; DVD-Video